Socioecological Factors Associated with Hypertension Awareness and Control Among Older Adults in Brazil and Colombia: Correlational Analysis from the International Mobility in Aging Study - Catherine M. Pirkle; Ricardo Oliveira Guerra; Fernando Gómez; Emmanuelle Belanger; Tetine Sentell (Global Heart, 2023)
Background: Hypertension awareness and control are understudied among older adults in middle-income countries, with limited work contextualizing awareness and control across layers of influence (individual to the community). Research on hypertension in Latin America is acknowledged as insufficient. Objectives: This study applies the socioecological model (SEM) to examine individual, interpersonal, institutional, and community factors related to hypertension awareness and control in older adults residing in Brazil and Colombia. It identifies groups of older adults more likely to be unaware of their condition and/or to have challenges achieving hypertension control. Methods: We analyzed International Mobility in Aging Study data of 803 community-dwelling adults 65–74 years from study sites in the two most populous countries in South America. The study framework was the socioecological model. Logistic regression models identified factors associated with hypertension awareness and control. Conclusions: Hypertension was prevalent in both samples (>70%), and awareness was high (>80%). Blood pressure control among diagnosed respondents was low: 30% in Brazil and 51% in Colombia. Factors across the socioecological model were associated with awareness and control, with notable differences across countries. Those with diabetes (OR 4.19, 95%CI 1.64–10.71) and insufficient incomes (OR: 1.85, 95%CI 1.03–3.31) were more likely to be aware of their hypertension. In Colombia, those reporting no community activity engagement were less likely to be aware compared to those reporting community activities. In Brazil, it was the opposite. Women (OR 1.66, 95%CI 1.12–2.46) and those reporting strolling shops and stores (OR 1.80, 95% CI 1.09–3.00) were significantly more likely to have their hypertension under control. In Brazil, those 70–75 were significantly less likely to have their hypertension under control compared to their younger counterparts. In Colombia, this was not observed. This paper highlights the importance of theory-based studies within unique Latin American contexts on hypertension and suggests novel opportunities for intervention.